COMMUNICATION AND EMPLOYEE JOB SATISFACTION IN MTN ZONAL OFFICE ONITSHA, ANAMBRA STATE, NIGERIA - Mikella, Nebolisa Chinwe; Lucky, Agazuma (Universitas Negeri Malang, 2024)
This study investigated the effect of communication on employee job satisfaction at MTN Zonal Office, Onitsha, Anambra State, Nigeria. Specifically, the objectives were to evaluate the effect of communication channels on employee job satisfaction, examine the influence of technological communication tools on employee job satisfaction, and investigate the effect of internal communication on employee job satisfaction. Conceptual reviews indicated that effective communication channels enhance clarity and employee alignment with organizational goals, while technological tools foster efficiency and inclusivity. Internal communication fosters trust and collaboration, leading to higher job satisfaction. The study employed a survey research design with a sample size of 50 employees using a complete enumeration sampling technique. Data were collected through structured questionnaires and analyzed using multiple regression analysis. Findings revealed a significant positive relationship between communication channels and employee job satisfaction (B = 0.456, p-value = 0.001), a significant influence of technological communication tools on employee job satisfaction (B = 0.527, p-value = 0.000), and a significant effect of internal communication on employee job satisfaction (B = 0.374, p-value = 0.000). The study concludes that communication is a critical factor in fostering job satisfaction. Recommendations include adopting advanced communication technologies, implementing regular feedback mechanisms, and conducting training programs to enhance communication effectiveness and employee engagement.